Electroencephalographic Findings in Pediatric Patients with Anti-N-Methyl-D-Aspartate Receptor Encephalitis: The San Diego Experience - Frederick, Aliya; Yang, Jennifer H.; Guido-Estrada, Natalie; Soria-Lopez, Jose; Sattar, Shifteh (Journal of Pediatric Epilepsy, 2020)
Diagnosing anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis clinically can be challenging. There is a growing interest in identifying specific electroencephalographic features to help guide early management. A retrospective chart review was conducted of pediatric patients admitted to Rady Children's Hospital between January 1, 2010 and April 1, 2017. We included patients with the diagnosis of encephalitis who underwent continuous video electroencephalogram (VEEG) for at least 12 hours, and presented with less than 14 days of symptoms. We compared the electroencephalographic features of non-rapid eye movement (NREM) sleep between patients with antibody confirmed anti-NMDAR encephalitis and patients with encephalitis from other etiologies. We identified seven patients who met our inclusion criteria, five of whom were diagnosed with anti-NMDAR encephalitis. Four of the five patients had a significant reduction in NREM sleep, while one patient had increased NREM sleep associated with clinical catatonia and hypersomnolence. Sleep was preserved in the two cases of nonimmune mediated encephalitis. Our results suggest that a prolonged VEEG to capture sleep coupled with clinical features can aid in early diagnosis and treatment of anti-NMDAR encephalitis, often before confirmatory antibody testing is available.
Keywords: anti-NMDA receptor encephalitis; anti-NMDAR encephalitis; electroencephalogram; NREM sleep